Kreativitas Guru Dalam Mengajar Di Masa Pandemi Covid-19 Terhadap Hasil Belajar Siswa Di SDK Paupire Ende - Berty Sadipun; Chatarina Novianti (Cetta: Jurnal Ilmu Pendidikan, 2021)
Based on the results of the study, there is a positive and significant effect of teacher creativity on student learning outcomes, it can be seen from the value of tcount (4.783) > ttable 1.69389 with a significance value of 0.000 <0.05, which means there is a significant effect of learning creativity variable on student learning outcomes. And the magnitude of the influence value seen from the output coefficient of determination (R2) is 0.43.3 or 43.3%. So it can be said that 43.3% of student learning outcomes are influenced by teacher creativity. While the remaining 56.7% is influenced by other variables not examined in this study, such as the teacher's role, teacher motivation, teacher attention and so on